The Influence Of Family Ownership On Tax Avoidance - Hartono, Hartono (Journal of Economics and Business (JECOMBI), 2024)
This study aims to analyze the influence of family ownership on tax avoidance and examine the role of Good Corporate Governance (GCG) as a mediating variable in this relationship. The study employs a quantitative approach with a panel data regression model, applied to manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) during the 2013–2020 period. The results indicate that family ownership does not have a significant effect on tax avoidance. Furthermore, GCG fails to mediate the relationship between family ownership and tax avoidance, with a mediation test probability value of 0.7572. These findings suggest that strategic decisions in family-owned companies are more influenced by family values than by formal governance mechanisms. The implications of this research highlight the importance of strengthening corporate governance practices that are more substantive and relevant to the characteristics of family businesses, through both regulatory oversight and internal improvements. This study provides both academic and practical contributions to the development of tax policies and governance in Indonesia.